Аnalysis of the tuberculosis situation in the Republic of Tajikistan - U. Yu. Sirodzhidinova; O. I. Bobokhodzhaev; Z. Sh. Dusmatova; F. O. Mirzoeva; K. I. Pirov; R. R. Dzhumaev (Туберкулез и болезни лёгких)
The paper analyzes the epidemiological indicators of tuberculosis among adults and children in the Republic of Tajikistan in 1994-2003. Despite the fact that the registered morbidity and mortality rates for tuberculosis (TB) have become stable in this country in the past 5 years, its burden has remained tense. Examination using a drug resistance test revealed that in 2009 there were 17 and 60% of patients with multidrug resistant TB among the new and recurrent cases, respectively. There were 68 cases of TB with broad drug resistance in the pathogen and only 10 patients had access to treatment. In 2009-2013, the proportion of HIV/TB patients accounted for 1.3-2.5%. Innovative technologies (GeneXpert, HAINtest, and MGIT) are finding increasing use for diagnosis and differential diagnosis; early detection of tuberculosis by fluorography and tuberculin diagnosis is being established. The efficiency of treatment in patients with tuberculosis with susceptibility and resistance in the pathogen was 88 and 66.7%, respectively.